2020
DOI: 10.1021/acschembio.0c00891
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ligand Preferences of the PHD1 Domain of Histone Demethylase KDM5A Reveals Tolerance for Modifications of the Q5 Residue of Histone 3

Abstract: Understanding the ligand preferences of epigenetic reader domains enables identification of modification states of chromatin with which these domains associate and can yield insight into recruitment and catalysis of chromatin-acting complexes. However, thorough exploration of the ligand preferences of reader domains is hindered by the limitations of traditional protein–ligand binding assays. Here, we evaluate the binding preferences of the PHD1 domain of histone demethylase KDM5A using the protein interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Collectively, our data suggest that H3 residues A1, R2, and K4 are the major determinants of H3 peptide binding, with smaller contributions from H3T3. Our recent study has also shown that H3Q5 is dispensable for binding as H3 Q5A peptide binds with similar affinity to WT H3 . These data suggest a finely tuned binding site with varying, methylation-dependent contributions to H3 binding and H3K4 methyl discrimination.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Collectively, our data suggest that H3 residues A1, R2, and K4 are the major determinants of H3 peptide binding, with smaller contributions from H3T3. Our recent study has also shown that H3Q5 is dispensable for binding as H3 Q5A peptide binds with similar affinity to WT H3 . These data suggest a finely tuned binding site with varying, methylation-dependent contributions to H3 binding and H3K4 methyl discrimination.…”
Section: Resultsmentioning
confidence: 53%
“…Our recent study has also shown that H3Q5 is dispensable for binding as H3 Q5A peptide binds with similar affinity to WT H3. 70 These data suggest a finely tuned binding site with varying, methylationdependent contributions to H3 binding and H3K4 methyl discrimination. However, the contributions of these residues to binding may not be conserved between KDM5 family PHD1 domains.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…For example, they found binding of BRD4 to di- and triacetylated H4 peptides was detected with their optimized protocol but not using a more conventional procedure. A recent innovation coupled a peptide array to a Matrix-Assisted Laser Desorption/Ionization (MALDI) MS readout . Peptides were immobilized on a gold surface using alkanethiolate chemistry such that each spot contained one histone peptide and a reporter peptide that can be deacetylated by KDAC8.…”
Section: Methods For Profiling Binding Preferences Of Specific Chroma...mentioning
confidence: 99%
“…A recent innovation coupled a peptide array to a Matrix-Assisted Laser Desorption/Ionization (MALDI) MS readout. 82 Peptides were immobilized on a gold surface using alkanethiolate chemistry such that each spot contained one histone peptide and a reporter peptide that can be deacetylated by KDAC8. A fusion protein of KDAC8 and a POI was exposed to the peptide array.…”
Section: Preferences Of Specific Chromatin Ptm Interactorsmentioning
confidence: 99%